STRATEGI SUPERVISE KEPALA MADRASAH KEPADA GURU DI MTSN 4 TABALONG - Chairul Echwan (CV. ADIBA AISHA AMIRA, 2025)
This research is motivated by the importance of supervision carried out by madrasa heads for teachers and the need for appropriate strategies to support its success. The aim of this research is to find out what the madrasa head's supervision strategy is for teachers and what the supporting and inhibiting factors are. The type of research used is field research with a qualitative descriptive approach. The research subjects were the head of the madrasa, deputy head of the madrasa for academic affairs and teachers. Furthermore, data collection techniques use observation, interviews and documentation. Then data analysis includes data reduction, data presentation and drawing conclusions/verification. The research results show that the Head of MTsN 4 Tabalong develops and guides teachers, provides information to teachers, and also builds a working network with stakeholders to collaborate to improve teacher quality. The madrasa head explains the role and targets to the maximum, carries out monitoring well and continuously, provides good support, provides motivation and inspiration to teachers, makes efforts to solve problems and provides solutions to teachers as a whole, so it can be concluded that the madrasa head's supervision strategy for teachers has been implemented well. The supporting factors are the teacher's condition, strong desire, and cooperative stakeholders. Meanwhile, the inhibiting factors are time, social jealousy, and low willingness to move on the part of some teachers.